The Comparative Study Between Calcium Hydroxide and Garlic Extract on Inhibitory Effect of Clinical Isolate Bacterial of Primary Teeth - Dewi, IAIA Krisna Kencana; Bramanti, I; Sudarso, ISR; Wahyunigsih, MSH; Wibawa, T (International Journal of Human and Health Sciences (IJHHS), 2020)
This study aimed to compare the antibacterial effectivity of calcium hydroxide and garlic extract by assessed the inhibitory effect on clinical isolate bacterial of necrotic primary teeth. Materials and methods: Clinical isolate bacterial of primary teeth were taken from the children who visited the Clinic of Pediatric Dentistry, Dental Hospital of UGM Prof Soedomo, Yogyakarta, Indonesia with age 4-7 years old. Aerobic and anaerobic bacteria were taken directly from 26 children who will undergo endodontic treatment with a diagnosis of pulp necrosis. The identification and isolation technique was done based on CLSI Standardized Method 2012 and Biochemical identification by Thermo Scientific RapID Systems 2010. There are 3 clinical isolates bacterial of necrotic primary teeth as reference for in vitro antibacterial activity testing and 2 bacteria as a comparison. Antibacterial effectivity of calcium hydroxide was examined by diffusion method by comparing calcium hydroxide, 20%, 40%, 60%, 80% concentration of garlic extract, and garlic filtrate. The sensitivity test result was taken after 24-48 hours of incubation by assessing the inhibitory zones around the well. Results: The measurement result of inhibitory diameter zone of Calcium hydroxide against Prevotella bivia was 30 mm, against Clostridium innocum was 30 mm, against Serratia marcescens was 23 mm. The inhibitory diameter zone of Calcium hydroxide against Clostridium perfringens as a comparative bacteria was 34 mm and 30 mm against Streptococcus mutans. Conclusion: All groups in this study have inhibitory effect against clinical isolate bacterial of necrotic primary teeth. The inhibitory effect of calcium hydroxide is greater than the inhibitory effect of garlic extract but lower when compared with garlic filtrate. International Journal of Human and Health Sciences Vol. 04 No. 04 October’20 Page : 282-286